PROBLEM-BASED LEARNING MODEL: IMPLEMENTATION IN MATHEMATICS LEARNING FLAT BUILT MATERIALS - Maningide, Meivilia Inke; Mangobi, James U. L.; Regar, Vivian E. (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The objective of this research is to ascertain the disparity in the mean learning outcomes between students instructed through the Problem Based Learning (PBL) approach and those instructed through the Direct Instruction (DI) approach. This study used a quasi-experimental approach, specifically the Posttest-Only Control Group design. The research was conducted at SMP Negeri 4 West Siau during the second semester of the 2023/2024 academic year. The participants of this study were selected from two homogeneous and identical classes: class VIIA, consisting of 14 students who received the Problem Based Learning (PBL) model treatment, and class VIIB, consisting of 14 students who received the Direct Instruction (DI) model treatment. The mean posttest score for the experimental group was 82.64, while the mean posttest score for the control group was 68.85. Conducting a data analysis using the t-test, the calculated t-value is 6.599, which is greater than the critical t-value of 2.056. Therefore, the choice is made to reject the null hypothesis (H0). Therefore, the Problem Based Learning (PBL) paradigm has the potential to enhance the overall academic performance of students in the subject of Bangun Datar